2007
DOI: 10.1083/jcb.200702080
|View full text |Cite
|
Sign up to set email alerts
|

α4β1 integrin and erythropoietin mediate temporally distinct steps in erythropoiesis: integrins in red cell development

Abstract: Erythropoietin (Epo) is essential for the terminal proliferation and differentiation of erythroid progenitor cells. Fibronectin is an important part of the erythroid niche, but its precise role in erythropoiesis is unknown. By culturing fetal liver erythroid progenitors, we show that fibronectin and Epo regulate erythroid proliferation in temporally distinct steps: an early Epo-dependent phase is followed by a fibronectin-dependent phase. In each phase, Epo and fibronectin promote expansion by preventing apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 28 publications
(36 reference statements)
6
60
0
Order By: Relevance
“…The initial stages of terminal erythroid maturation are highly dependent on erythropoietin (1), whose roles in activation of erythroid specific genes, terminal proliferation, and protection against apoptosis are well understood (2). This is followed by an erythropoietin-independent, fibronectin-dependent phase where survival and proliferation of the erythroblasts require signaling by ␣4␤1 integrins (3). Upon erythropoietin stimulation, CFU-E progenitors undergo 4 -5 cell divisions accompanied by a decrease in cell size, increase in hemoglobin content, and nuclear condensation followed by withdrawal from the cell cycle (4).…”
mentioning
confidence: 99%
“…The initial stages of terminal erythroid maturation are highly dependent on erythropoietin (1), whose roles in activation of erythroid specific genes, terminal proliferation, and protection against apoptosis are well understood (2). This is followed by an erythropoietin-independent, fibronectin-dependent phase where survival and proliferation of the erythroblasts require signaling by ␣4␤1 integrins (3). Upon erythropoietin stimulation, CFU-E progenitors undergo 4 -5 cell divisions accompanied by a decrease in cell size, increase in hemoglobin content, and nuclear condensation followed by withdrawal from the cell cycle (4).…”
mentioning
confidence: 99%
“…The ECM in the hematopoietic microenvironment is composed of various macromolecules, such as fibronectin (FN), collagens, laminins, and proteoglycans. Among them, FN is one of the most important parts of the microenvironment niche (7)(8)(9)(10)(11). Also, in erythropoiesis, the importance of the adhesion of erythroid progenitors to FN via the FN receptors VLA-4 and VLA-5 has been reported (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Among them, FN is one of the most important parts of the microenvironment niche (7)(8)(9)(10)(11). Also, in erythropoiesis, the importance of the adhesion of erythroid progenitors to FN via the FN receptors VLA-4 and VLA-5 has been reported (11)(12)(13)(14)(15)(16). However, the substantial role of these FN receptors and their functional assignment in erythroid differentiation are not yet fully understood.…”
mentioning
confidence: 99%
“…Vice versa, ECM cultured AT-and SN-cells showed reduced myeloid colony formation regarding CFU-G, CFU-M and CFU-GM (Figure 1f). It has been demonstrated that erythropoiesis requires ITGb1 mediated FN adhesion [10] and ITGb3 expression is a marker for erythroid commitment [7]. To test whether erythroid lineage commitment is associated with ITGb3 expression in our ex-vivo ECM culture, we separated CD34 + ITGb3 + and CD34 + ITGb3 -cells.…”
Section: Resultsmentioning
confidence: 99%
“…Following this line, ECM proteins exhibit multiple binding sites for colony-stimulating factors (CSFs), which can trigger myeloid lineage commitment [8] [9]. Additionally, ECM proteins like fibronectin (FN) were found to be essential for erythropoiesis [10] and pro-erythroid growth factors like IL-3 and BMP4 are incorporated in ECM scaffolds [5]. Therefore, we asked whether BM-mimetic ECM scaffolds might trigger erythropoiesis when culturing HSPC.…”
Section: Introductionmentioning
confidence: 99%